2020
DOI: 10.3126/medphoenix.v5i1.31387
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Self-rated Oral Health Knowledge, Attitudes and Practices in a Marginalized Community From Eastern Nepal

Abstract: Background: Oral health knowledge, attitude and practices are essential components of general human health, and its assessment can serve to identify risk factors and design appropriate behavior modification strategies. However, studies on poor and marginalized people who have a higher proportion of oral health problems are relatively scarce. This study aimed to assess the differences in level of knowledge, attitudes and practices between the under-privileged and the privileged population of a rural location in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We did not take the highest grade of basic level schools as the students of Grade Eight would graduate to secondary schools and our intervention would not be able to capture those. We took the reference prevalence of dental caries as 60% among school children while calculating the estimated sample size [ 9 ]. We also considered 95% confidence interval and 80% of the power of the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not take the highest grade of basic level schools as the students of Grade Eight would graduate to secondary schools and our intervention would not be able to capture those. We took the reference prevalence of dental caries as 60% among school children while calculating the estimated sample size [ 9 ]. We also considered 95% confidence interval and 80% of the power of the study.…”
Section: Methodsmentioning
confidence: 99%
“…To add further, 58% of the schoolchildren aged between 5–6 years were affected by dental caries. The study also revealed that oral health problems were the prime reason of missing school in Nepal, where 32% of the students missed their school due to dental pain [ 9 ].…”
Section: Introductionmentioning
confidence: 99%